2018
DOI: 10.1002/anie.201811318
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Structure Determination of Microcrystalline Molecular Compounds Using Electron Diffraction

Abstract: Chemists of all fields currently publish about 50 000 crystal structures per year, the vast majority of which are X‐ray structures. We determined two molecular structures by employing electron rather than X‐ray diffraction. For this purpose, an EIGER hybrid pixel detector was fitted to a transmission electron microscope, yielding an electron diffractometer. The structure of a new methylene blue derivative was determined at 0.9 Å resolution from a crystal smaller than 1×2 μm 2 . Several t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
247
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(255 citation statements)
references
References 48 publications
4
247
0
4
Order By: Relevance
“…TheGrüne group were able to elucidate the structure of acetaminophen (1)f rom ac ommercial flu relief medicine in the presence of several other pharmaceutically active and non-active ingredients.I na ddition, as ingle needle (approximately 1 2 mm 2 and hence too small for standard SXRD measurement) of anovel methylene blue derivative provided ad ataset of 0.9 resolution from its mother liquor within four hours. [5] Similar impressive results were independently reported by Gonen and co-workers,who analyzed atotal of 11 different, biologically active,o rganic compounds.F rom ac ommercial sample of progesterone (2), estimated to be 20 years old, approximately 1mgw as ground between two glass slides to produce af ine powder.A fter depositing the sample on aholey carbon-copper grid, it was cooled to liquid nitrogen temperature and transferred to aT hermo Fisher Talos Arctica cryoelectron microscope.U pon imaging,s everal hundreds of nanocrystals suitable for diffraction and with sufficient resolution to determine the connectivity could be identified. Thed iffraction of one of these nanocrystals was good enough to collect adataset of 1.0 resolution of steroid 2,with the molecular structure obtained at atomic resolution within 30 minutes.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…TheGrüne group were able to elucidate the structure of acetaminophen (1)f rom ac ommercial flu relief medicine in the presence of several other pharmaceutically active and non-active ingredients.I na ddition, as ingle needle (approximately 1 2 mm 2 and hence too small for standard SXRD measurement) of anovel methylene blue derivative provided ad ataset of 0.9 resolution from its mother liquor within four hours. [5] Similar impressive results were independently reported by Gonen and co-workers,who analyzed atotal of 11 different, biologically active,o rganic compounds.F rom ac ommercial sample of progesterone (2), estimated to be 20 years old, approximately 1mgw as ground between two glass slides to produce af ine powder.A fter depositing the sample on aholey carbon-copper grid, it was cooled to liquid nitrogen temperature and transferred to aT hermo Fisher Talos Arctica cryoelectron microscope.U pon imaging,s everal hundreds of nanocrystals suitable for diffraction and with sufficient resolution to determine the connectivity could be identified. Thed iffraction of one of these nanocrystals was good enough to collect adataset of 1.0 resolution of steroid 2,with the molecular structure obtained at atomic resolution within 30 minutes.…”
supporting
confidence: 77%
“…Thec ompound is found in am ore or less ordered fashion within the pores, bound by weak interactions.A lthough the CS method only needs minute amounts of the analyte and circumvents the crystallization procedure,the soaking of the sponge needs to be optimized and not all classes of compounds are compatible with the commonly used coordination networks. [3a,b] In two recent publications,b oth Grüne et al [5] as well as Gonen and co-workers [6] convincingly demonstrated the potential application of microcrystal electron diffraction (MicroED) to elucidate the structures of small organic molecules.M icroED was originally developed to study large biological macromolecules,specifically proteins. [7] In contrast to SXRD,anelectron beam is used to observe the scattering of crystals 1/6000th the volume of acrystal typically used for SXRD.I nt hese two new studies,t he researchers show that the technique can be applied to obtain the molecular structure of nanocrystals present in finely graded powders,a sr eadily obtained from chemical suppliers and even from seemingly amorphous films of chromatography fractions in ascintillation vial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, mixtures of crystals within a single grid or contaminated samples can be studied without significant modifications by assigning each found lattice to one of the contained sample classes using multiple indexing runs or direct classification of diffraction patterns 36,47 . It is moreover not only limited to proteins but encompasses all nanocrystalline compounds, such as pharmaceuticals 47,48 or porous materials 23,49,50 . Augmenting parallel-beam crystallography with coherent scanning diffraction techniques such as coherent nano-area diffraction, convergent-beam diffraction or low-dose ptychography might be a viable way to obtain Bragg reflection phase information 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the recent advancement in complementary metal-oxide semiconductor and hybrid detector technology, it is now feasible to collect diffraction data in movie mode while continuously rotating the crystal (5,12,17). Benefiting from these technological advances, data collection and structure refinement can now be performed within hours (18,19). Furthermore, peptide structures have been solved ab initio using high-resolution MicroED data (20,21).…”
Section: Introductionmentioning
confidence: 99%